Penning trap mass measurements utilizing highly charged ions as a path to benchmark isospin-symmetry breaking corrections in 74Rb - Malbrunot-Ettenauer, Stephan; Brunner, Thomas; Chowdhury, U.; Gallant, Aaron; Simon, Vanessa Véronique; Brodeur, Maxime; Chaudhuri, A.; Mané, E.; Simon, Martin C.; Andreoiu, C.; Audi, G.; Crespo López-Urrutia, J. R.; et al. (Physical review. C, Nuclear physics, 2015)
Penning trap mass measurements of neutron-deficient Rb isotopes have been performed at TRIUMF's Ion Trap for Atomic and Nuclear Science (TITAN) facility by utilizing highly charged ions (HCIs). As imperative for a new approach with significant gain in measurement precision, experimental procedures, and systematic uncertainties are discussed in detail. Among the investigated nuclides, the superallowed nuclear β emitter 74Rb will especially benefit from the advantage offered by HCI because the limited attainable precision owing to its short half-life (T1/2=65 ms) represents a challenge for conventional Penning trap mass spectrometry. Motivated by an updated QEC value for 74Rb of 10 416.8(3.9) keV and its large isospin-symmetry breaking corrections, we present a new test to benchmark the consistency between theoretical models of isospin-symmetry breaking corrections in superallowed decays, the conserved vector current hypothesis, and experimental data.
Gesehen am 05.06.2020
Im Titel ist "74" in 74Rb hochgestellt